The Influence of Financial Literacy, Age, and Gender on Sustainable Investment Preferences Among Millennial Students - Fitri, Fitri (Green Publisher, 2023)
This research investigates the relationship between financial literacy, gender, and age on sustainable investment preferences among millennial students. The variables examined include financial education (X1), age (X2), gender (X3), and sustainable investment preferences (Y1), which constitute a literature review in the field of financial management. The aim of this article is to provide an understanding of how financial literacy, age, and gender influence sustainable investment preferences in the millennial generation. The research method employs a quantitative method to analyze survey data collected from millennial students. The study's findings are anticipated to offer an insight into the factors influencing sustainable financial decisions and social responsibility among millennial students. The findings of this article are as follows: 1) Financial education influences Sustainable Investment Preferences; 2) age affects Sustainable Investment Preferences; 3) gender has an impact on Sustainable Investment Preferences.